High-throughput sequencing contributes to the diagnosis of tubulopathies and familial hypercalcemia hypocalciuria in adults - Hureaux, Marguerite; Schaefer, Franz (Kidney international, 2019)
Hereditary tubulopathies are rare diseases with unknown prevalence in adults. Often diagnosed in childhood, hereditary tubulopathies can nevertheless be evoked in adults. Precise diagnosis can be difficult or delayed due to insidious development of symptoms, comorbidities and polypharmacy. Here we evaluated the diagnostic value of a specific panel of known genes implicated in tubulopathies in adult patients and compared to our data obtained in children. To do this we analyzed 1033 non-related adult patients of which 744 had a clinical diagnosis of tubulopathy and 289 had a diagnosis of familial hypercalcemia with hypocalciuria recruited by three European reference centers. Three-quarters of our tubulopathies cohort included individuals with clinical suspicion of Gitelman syndrome, kidney hypophosphatemia and kidney tubular acidosis. We detected pathogenic variants in 26 different genes confirming a genetic diagnosis of tubulopathy in 29% of cases. In 16 cases (2.1%) the genetic testing changed the clinical diagnosis. The diagnosis of familial hypercalcemia with hypocalciuria was confirmed in 12% of cases. Thus, our work demonstrates the genetic origin of tubulopathies in one out of three adult patients, half of the rate observed in children. Hence, establishing a precise diagnosis is crucial for patients, in order to guide care, to survey and prevent chronic complications, and for genetic counselling. At the same time, this work enhances our understanding of complex phenotypes and enriches the database with the causal variants described.